David and Goliath a comparison of XML-enabled and native XML data management techniques. - Serna, Ainhoa
Due to the great increase of data in XML format, companies increasingly have to face the issue of how to manage this data efficiently. To do this it is important to take advantage of XML's potential and to integrate with applications that access data stored in relational database management systems (RDBMS).